Łowiec, łowca, łowiectwo… w polszczyźnie dawnej i współczesnej (na materiale leksykograficznym) - Janicka-Szyszko, Renata (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
The article presents an attempt at determining how the Polish language was affected by hunting, which has been part of the Polish economy and culture for centuries. Linguistic material extracted from lexicographic and online sources was described and characterised for this purpose, which allowed for enriching the content related to contemporary Polish. The analysis of how the studied vocabulary is registered indicates a diversity in its functionality, while an overview of its use by the members of the hunting community proves that some of the words are being extracted from language archives and used as part of the names of hunting clubs or hunting magazines. Present among the hunting-related onyms are chrematonyms, anthroponyms and toponyms that show hunting’s historical links to people and places. Hunting-related proverbs conceptualise the diverse image of hunters; the diverse linguistic elements collected for and described in the study reflect the realities of hunting. The lexis, proverbs, place names and surnames morphologically related to hunting wild animals constitute a testament to the significant role that this area of life played and still plays in Polish culture.